Capacitated Location-Routing Problem for a Combined Manned-Unmanned Teaming System using Lagrangian Relaxation and Location-based Heuristic - Lee, Jinho (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
The integration of unmanned systems into modern military operations has heightened the importance of manned-unmanned teaming (MUM-T), particularly in maritime surveillance missions. This study addresses a critical challenge in MUM-T operations: Optimally locating manned surface vessels and assigning reconnaissance routes for unmanned surface vehicles (USVs) under capacity constraints. We formulate this model as a capacitated Location-Routing Problem and propose a two-phase solution framework. The first phase solves three variants of the facility location problem—the uncapacitated facility location problem, p-median problem, and capacitated facility location problem—using Lagrangian relaxation. The second phase applies a location-based heuristic to generate efficient routing plans for USVs. Computational experiments using benchmark datasets demonstrate the effectiveness of the proposed approach, particularly highlighting efficiency in the uncapacitated case. This study contributes to logistics planning for hybrid manned-unmanned systems by adapting classical optimization tools to military reconnaissance scenarios.